TRENDS AND CHALLENGES IN ISLAMIC EDUCATION LEARNING MEDIA FOR EARLY CHILDHOOD: A SYSTEMATIC LITERATURE REVIEW - Arif, Muhamad; Chapakiya, Suraiya; Masturoh, Umi (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2025)
The urgency of selecting effective Islamic Education learning media in the era of digital technology for early childhood education is an inevitability that cannot be postponed; a learning media based on multisensory digital technology because this media can improve understanding and retention of information, support various learning styles and are in accordance with the digital era so that it can combine audio, visual, kinesthetic, local wisdom and technology. This study aims to analyze the existence of Islamic Education learning media for early childhood, challenges and opportunities through systematic literature review research methods, the process of searching for research results using keywords in Indonesian and English, namely: Islamic Education